Serum levels of VEGF and MCSF in HER2+ / HER2- breast cancer patients with metronomic neoadjuvant chemotherapy - Roberto J. Arai; Vanessa Petry; Paulo M. Hoff; Max S. Mano (BMC, 2018)
Abstract Metronomic therapy has been gaining importance in the neoadjuvant setting of breast cancer treatment. Its clinical benefits may involve antiangiogenic machinery. Cancer cells induce angiogenesis to support tumor growth by secreting factors, such as vascular endothelial growth factor (VEGF). In breast cancer, Trastuzumab (TZM) based treatment is of key importance and is believed to reduce diameter and volume of blood vessels as well as vascular permeability. Here in we investigated serum levels of angiogenic factors VEGF and MCSF in patients receiving metronomic neoadjuvant therapy with or without TZM. We observed in HER2+ cohort stable levels of MCSF through treatment, whereas VEGF trend was of decreasing levels. In HER2- cohort we observed increasing levels of MCSF and VEGF trend. Overall, HER2+ patients had better pathological response to treatment. These findings suggest that angiogenic pathway may be involved in TZM anti-tumoral effect in the neoadjuvant setting.